Neuroinflammation in Schizophrenia - Feytie Magda Mawey; Azimatul Karimah; Erlyn Limoa; Muhammad Nazmuddin (Jurnal Psikiatri Surabaya, 2021)
Schizophrenia is a chronic debilitating mental illness. In many aspects, the neuropathology of schizophrenia is closely associated with neuroinflammation, especially microglial activation. Microglial hyperactivity, which is characterized by the predominant release of proinflammatory cytokines serves as the basis of the neuroinflammation hypothesis in schizophrenia. The enhanced inflammatory induce neuronal susceptibility to oxidative stress and trigger, glutamatergic synaptic dysregulation, especially in the mesolimbic and mesocortical pathways. Many in vitro studies, in vivo animal evidence, post-mortem examinations, neuroimaging evaluations with Positron Emission Tomography (PET), anti-inflammatory and antipsychotic use converge upon the central role of microglial activation and proinflammatory cytokines as common of features schizophrenia.